Strategic Business Alliances Vol. 2: concepts, laws, practices & precedents - Igwe, J.U.K (Abuja, Nigeria, 2008)
This book is the investor's roadmap on legal and regulatory incentives for trade and investment in Nigeria. The book also provides practical linkage between the law and development finance.
Includes index
usc 01/12/2021
Loans
Keywords: Business law; Energy regulation; Tax incentives; Nigeria